Visual Inspection of Historical Buildings Using Micro UAV - Kaamin Masiri; Idris Noor Azyyati; Mohd Bukari Saifullizan; Ali Zaurin; Samion Norhafiza; Anjang Ahmad Mustaffa (MATEC Web of Conferences, 2017)
The historical building is one of the country’s heritage that needs to be taken care of failures in design and structure. Damage or dilapidation study that conducted by Conservation of Historical Building Guide Lines that practices for documentation any problems and defects in buildings. The stages to be followed to determine the damage was shooting photos for every element studied. Photo has been taken directly or by using stair for higher parts of structures. Inspection of the historical building should be emphasized to ensure that the building is in a safe condition for long periods. This research aims is to investigate the historical building defects by using Unmanned Aerial Vehicle (UAV) to identify the type of defects occur at the exterior structure of museum. The case study is building of Perak Museum that located at Taiping, Perak. The process involved in this study are planning and preparation before the flight, data acquisition using UAV, image processing and analyzing data from video to image. The result of analysis, a total numbers of 91 locations have been identified and documented suffer from defects or faults such as frame decayed, vegetation, perforated pipe and crack. All defects information obtained suing UAV visual inspection can help the museum maintainance team for conservation and maintainace work.